Membangun Branding Sekolah Islam: Studi Komunikasi Strategis dalam Manajemen Pendidikan Islam - Sari, Ratna (Kordinat: Jurnal Komunikasi antar Perguruan Tinggi Agama Islam, 2025)
The purpose of this study was to understand how the branding management strategy of Insan Cendekia Islamic School was being implemented, including its socialization management and institutional management, through the use of an international curriculum. The school was changing the public mindset about Islamic schools. The management of Insan Cendekia Islamic School was developing a strategic branding communication approach to build a positive reputation and attract prospective students and their parents. In facing the increasingly tight competition in the education sector, Islamic schools were needing to establish a strong identity in order to remain relevant and become a top choice within society. The success in building a brand was not only relying on visual elements such as logos and slogans, but was also reflecting Islamic values that were being integrated into the school’s culture, curriculum, and the quality of its educational services. The results of the study showed that schools with strong branding were tending to gain higher trust from the community and were able to maintain the loyalty of students and alumni. Moreover, the optimal use of digital communication and active involvement in the community were becoming important factors in strengthening the image of Islamic schools. Therefore, branding was not merely being seen as a marketing strategy, but as an essential part of Islamic education management that was focusing on sustainability and institutional development for the future. This study revealed that Insan Cendekia Islamic School, which was succeeding in building strong branding, was applying various communication strategies, including: the use of digital media and social media, where the school was actively using digital platforms to promote its programs and activities in order to increase visibility and appeal to the wider public; the application of storytelling in marketing, which was proving effective in building an engaging brand, even though it was not yet fully optimized by many Islamic schools; the development of strategic partnerships, which was involving collaboration with pesantren, Islamic universities, and other educational institutions to enhance the school’s credibility and reputation; and the improvement of education quality and services, which was focusing on strengthening the quality of learning and school services to build a positive image in the eyes of the public.